2004
DOI: 10.1111/j.1365-3040.2005.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity for drought resistance in wild emmer wheat and its ecogeographical associations

Abstract: Wild emmer wheat ( Triticum turgidum spp. dicoccoides (Körn.) Thell.), the tetraploid progenitor of cultivated wheat, is a potential source for various agronomical traits, including drought resistance. The objectives of this study were to characterize (1) the genetic diversity for drought resistance in wild emmer wheat, and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 53 publications
6
137
1
Order By: Relevance
“…Although effects of flowering and maturation time on fitness in our study were found to be indirect and mediated by other traits, under drought, plants that flowered and set seeds earlier had higher fitness. Similarly, early flowering was associated with higher fitness under experimentally induced drought stress in the study by Peleg et al (2005). Surprisingly, in our study, plants from arid range location HA flowered and produced seeds later than the plants from the two more mesic core locations (Table 2 and Figure 4).…”
Section: Discussioncontrasting
confidence: 41%
“…Although effects of flowering and maturation time on fitness in our study were found to be indirect and mediated by other traits, under drought, plants that flowered and set seeds earlier had higher fitness. Similarly, early flowering was associated with higher fitness under experimentally induced drought stress in the study by Peleg et al (2005). Surprisingly, in our study, plants from arid range location HA flowered and produced seeds later than the plants from the two more mesic core locations (Table 2 and Figure 4).…”
Section: Discussioncontrasting
confidence: 41%
“…Other numbers correspond to 'LocationGenotype' identification numbers from the University of Haifa (UH) wheat germplasm collection (Nevo and Beiles 1989;Peleg et al 2005) and to varieties from the University of Bologna T. dicoccum collection (MG and IDG), seeds of which were kindly provided by Dr. Marco Maccaferri (University of Bologna, Italy). Theor Appl Genet.…”
Section: Figmentioning
confidence: 99%
“…Higher activity of the enzymes was in line with higher levels of WSCs identified in them-acc 14004 under irrigated and acc 7079 under rain-fed conditions. The observation of such a trend in these wild accessions may partly be due to the influence of environment where they originated and later evolved, i.e., eastern Mediterranean region, characterized by a long, hot dry summer and a short, mild wet winter with fluctuating amounts and distribution of rainfall (Loss and Siddique 1994;Peleg et al 2005).…”
Section: Discussionmentioning
confidence: 99%